Hak Konstitusional Masyarakat Lokal di Industri Pertambangan: Analisis Perbandingan Uganda dan Indonesia - Peace Patricia Ondoa; Paul Atagamen Aidonojie (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2026)
In Uganda and Indonesia, there is no doubt that the extractive industry has been engaged in severe activities in the oil, coal, nickel, tin, and gas sectors, most notably in the areas where these mineral resources are situated. However, although there is a constitutional framework on the rights of host communities in Indonesia and Uganda's extractive sector, these rights seem not to be fully realized in favor of the host communities of the extractive industry. It is in this study examines how Uganda and Indonesia protect the rights of host communities in the extractive industry. It finds significant challenges, including inadequate compensation, limited access to information, and low community participation levels in governance related to extractive industry activities. The findings show differences in the effectiveness of constitutional protections and enforcement in both countries. The study stresses the necessity of stronger legal safeguards and greater community engagement in the extractive sector for sustainable development. Moreover, the research emphasizes the necessity to integrate human rights in the planning and execution of extractive projects. The Study therefore recommends that there is a need to encourage a collaborative mindset between the state, industry stakeholders, and local communities to create a more equitable framework for resource management in Uganda and Indonesia.